An Analytical Solution for a Redundant Manipulator with Seven Degrees of Freedom - Takashi Nammoto; Kazuhiro Kosuge (International Journal of Automation and Smart Technology, 2012)
In this paper, an analytical solution for the inverse kinematics of a redundant manipulator with seven degrees of freedom and an offset rotation axis is presented. We provide a model for the redundant manipulator and introduce its self-motion. Considering geometric symmetry, sixteen sets of manipulator joint angles are obtained at once. Avoidance of singularities and obstacles is illustrated by simulation results.